COMPARATIVE EFFECT OF SELECTED BIO AND MINERAL FERTILIZERS ON THE GROWTH AND YIELD COMPONENTS OF TWO MAIZE CULTIVARS IN ALFISOLS OF SOUTHWESTERN NIGERIA - Oyebamiji, K.J.; Awodun, M.A.; Ayeni, L.S.; Ayelari, O.P.; Adeyemo, J.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
Field studies were carried out at the Teaching and Research Farm of Joseph Ayo Babalola University, Ikeji-Arakeji, Osun State, Nigeria, to compare the effect of selected biofertilizers and NPK 15:15:15 fertilizer on growth and yield components of two maize cultivars during 2022 rainy and dry seasons. The treatments consisted of three (3) biofertilizers (Pseudomonas (P), Nitrobacter (N), and Klesbisiella (K) at 40 and 50L/ha), NPK 15:15:15 fertilizer (at 250 kg/ha) and a control (CT).The plot of 5m x 5m was used with an alleyway of 0.5m and arranged in a randomized complete block design (RCBD) with four replications. The growth parameters were collected at 50% flowering while the yield parameters were determined at the maturity stage. Both varieties demonstrated reduced growth parameters during the dry seasons compared to the rainy seasons. The overall performance gap between the two varieties remained relatively small across both seasons. SAMAZ-52 had a slight advantage over OBA, but OBA could also perform adequately under varying conditions. In nutrient uptake, all the treatments significantly (P<0.05) increased N, P except K40 and N40, Ca except K40, Mg, Mn, Fe, Cu, and Zn compared with control. SAMAZ significantly increased (P<0.05) N, P, K, and Ca except P50, Mg except K50, NPK and P40, Mn, Fe, and Zn except N50. The increase in grain yield compared with control in OBA Super was 36% for K50, 41% for NPK, 38% for P50, 26% for K40, 33% for N50, 24% for P40, and 38% for N40, while SAMAZ cultivar recorded 37% for K50, 48% for NPK, 40% for P50, 30% for K40, 35% for N50, 36% for P40, and 40% for N40 indicating that Pseudomonas, Nitrobacter and Klesbisiella could be used to increase maize especially SAMAZ-52 variety production in southwestern Nigeria especially P50.